Paranoid - Jackson, Lisa (Thorndike, Maine : Center Point Large Print, 2019)
"Some people in Rachel Gaston's small hometown of Edgewater, Oregon, think she got away with murder twenty years ago when she mistook a real gun for a toy. As that deadly anniversary approaches, she'll need to find the truth ... before it finds her"--
There are people in Edgewater, Oregon, who think that Rachel Gaston got away with murder when she shot and killed her brother in a teenage game. That was twenty years ago, and Rachel is moving on, trying to put the guilt of what happened behind her. On the anniversary of her brother's death she receives a text message: I forgive you. Then she begins receiving midnight phone calls from a blocked number. Are these happenings malicious? Genuinely forgiving? Or is Rachel just being paranoid? -- adapted from back cover
Regular print version previously published by: Kensington Publishing Corp
Keywords: Manslaughter -- Fiction; Large type books; Accidents -- Fiction; Brothers -- Death -- Fiction; Stalking victims -- Fiction; Paranoia -- Fiction; Guilt -- Fiction; Oregon -- Fiction; Large type books